Effect of Musical Therapy on Malondialdehyde Levels on Male Mice Brain Tissue - Farindra, Irmawan; Muhammad, Akbar Reza; Algristian, Hafid; Rusdi, Warda Elmaida; Yuniati, Dyah (UNUSA Press, 2024)
Introduction: An example of a non-pharmacological therapy that is currently being developed is music therapy. The serenity created from classical music and murottal therapy is good for therapy performance, accelerating the healing process, and also reducing stress level. Objective: The aim of this study was to examine the effects of classical music